IMPLEMENTASI PERMAINAN JEPIT BAJU UNTUK MENINGKATKAN HAFALAN HURUF HIJAIYAH KELOMPOK A DI RA NURUR RAHMAH SUMBER ANYAR MLANDINGAN - Fatimatus Zahro (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2020)
This study presents the use of clothes pinning games to improve memorization of hijaiyah letters in RA Nurur Rahmah Group A Sumber Anyar Mlandingan with 14 students. The purposes of this study were 1) to know the process of implementing clothes pinning games in improving memorization of hijaiyah letters. 2) to find out the results of the implementation of playing activities by using clothes pinches to improve memorization of hijaiyah letters. The method used is by using the classroom action research. This study uses a model from Carr and Kemmis using 4 stages, namely planning, implementation, observation and reflection. The results of this study are: 1) The process of implementing the clothes pinning game starts from the child clamping the miniature clothes in order, then the child is accompanied by the teacher to mention and designate hijaiyah letters. 2) The pre cycle results reached 28% completeness. After taking the action, namely by using clothes pinning clothes, the results of Cycle I were 64% and Cycle II increased to 85%. Clothes Pinch; Hijaiyah letters